Reparative properties of human glioblastoma cells after single exposure to a wide range of X-ray doses - Pavlova, Galina; Belyashova, Alexandra; Savchenko, Ekaterina; Panteleev, Dmitri; Shamadykova, Dzhirgala; Nikolaeva, Anna; Pavlova, Svetlana; Revishchin, Alexander; Golbin, Denis; Potapov, Alexander; Antipina, Natalia; Golanov, Andrey (Frontiers in Oncology, 2022)
Radiation therapy induces double-stranded DNA breaks in tumor cells, which leads to their death. A fraction of glioblastoma cells repair such breaks and reinitiate tumor growth. It was necessary to identify the relationship between high radiation doses and the proliferative activity of glioblastoma cells, and to evaluate the contribution of DNA repair pathways, homologous recombination (HR), and nonhomologous end joining (NHEJ) to tumor-cell recovery. We demonstrated that the GO1 culture derived from glioblastoma cells from Patient G, who had previously been irradiated, proved to be less sensitive to radiation than the Sus\fP2 glioblastoma culture was from Patient S, who had not been exposed to radiation before. GO1 cell proliferation decreased with radiation dose, and MTT decreased to 35% after a single exposure to 125 Gγ. The proliferative potential of glioblastoma culture Sus\fP2 decreased to 35% after exposure to 5 Gγ. At low radiation doses, cell proliferation and the expression of RAD51 were decreased; at high doses, cell proliferation was correlated with Ku70 protein expression. Therefore, HR and NHEJ are involved in DNA break repair after exposure to different radiation doses. Low doses induce HR, while higher doses induce the faster but less accurate NHEJ pathway of double-stranded DNA break repair.